Tai Chi Ameliorates Coronary Heart Disease by Affecting Serum Levels of miR-24 and miR-155 - Li, Yang; Zhang, Haiyang; Wang, Yushi (Frontiers in Physiology, 2019)
The protective role of Tai Chi in coronary heart disease (CHD) patients has been widely reported. However, the exact molecular mechanism remains unclear. Serum miR-24 and miR-155 levels have been found to be responsible for CHD severity. Thus, the effects of Tai Chi on CHD were explored by measuring serum miR-24 and miR-155 levels. A total of 326 CHD patients were evenly divided into the Tai Chi (TG) and control (CG) groups. The activities of Daily Living Ability (ADL) and Exercise of Self-Care Agency (ESCA) scores between the two groups of patients were compared. Left ventricular ejection fraction (LVEF), SF-36 life quality, Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) were also measured. Serum miR-24 and miR-155 levels were measured by real-time qPCR. After a 6-month Tai Chi intervention, the ESCA, ADL, LVEF and SF-36 scores in the TG group were higher than those in the CG group (p < 0.05). The recovery time of arrhythmia, atrioventricular block and hospital stay, and SAS and SDS scores in the TG group were shorter than those in the CG group (p < 0.05). Serum levels of miR-24 and miR-155 in the TG group were also lower than in CG group (p < 0.05). In addition, they were negatively associated with the ESCA, ADL, LVEF and SF-36 scores, and had adverse effects on health-related quality of life. Taken together, our findings indicated that Tai Chi improved CHD prognosis by affecting serum levels of miR-24 and miR-155.